INVESTING IN TRANSPARENCY: HOW CAPITAL INVESTMENT, ENVIRONMENTAL SPENDING, AND MEDIA ATTENTION DRIVE CARBON EMISSION DISCLOSURE - Prasetyo Tyas Pradana; Nanik Sri Utaminingsih (Politeknik Negeri Ambon, 2026)
Introduction: This study examines the effects of profitability, capital expenditure, and environmental costs on carbon emissions disclosure (CED) among companies in Indonesia's basic materials, energy, and industrial sectors from 2019 to 2023. Media exposure is introduced as a moderating variable to explore its role in strengthening these relationships. Guided by stakeholder theory, this research addresses gaps in prior studies by investigating underexplored determinants, particularly environmental cost, and contextualizing their relevance within the Indonesian market.Methods: The study employs a quantitative approach, analyzing secondary data from the annual and sustainability reports of 27 companies. The hypotheses were tested using panel data regression and Moderated Regression Analysis (MRA).Results: The findings reveal that profitability, capital expenditure, and environmental cost have a positive and significant effect on carbon emission disclosure. Furthermore, media exposure significantly strengthens these relationships by increasing public scrutiny and encouraging greater corporate transparency.Conclusion and Suggestion: The study concludes that both internal financial factors and external stakeholder pressure contribute to improving carbon emission disclosure practices among Indonesian companies. Therefore, companies are encouraged to strengthen environmental reporting and transparency to support sustainable business practices and meet stakeholder expectations. Keywords: Capital Expenditure; Carbon Emission Disclosure; Environmental Cost; Media Exposure; Profitability.